Optimizing modeling the multilayer coextrusion flow of non-newtonian fluids through rectangular ducts: appropriate shear rate definition for a local power law formulation (2024)
The accuracy of viscosity predictions is a crucial aspect of polymer melt flow modeling and essential for the design of coextrusion die systems. In the field of non-Newtonian fluid modeling for coextrusion flows through rectangular ducts, significant progress has been made in understanding multilayer flow dynamics. Our fundamental research, employing numerical techniques such as the shooting method, finite element method, and finite difference method for flow evaluation, has established a critical base for the field. Our current research advances fluid dynamics by refining our existing numerical solver, specifically developed for multilayer coextrusion flows. We aim to enhance the solver’s performance by implementing more sophisticated calculations of shear rates that go beyond the traditional approach. The traditional approach often relies on average flow velocities and channel heights, which can underrepresent the complexity of experimentally studied polymer multilayer flows. Our study systematically compares various definitions for characteristic shear rates to describe the local shear rate dependent viscosity behavior using, for instance, a local power law model. A thorough error analysis quantifies the accuracy of each model and its predictive limitations for industrially relevant material combinations and operating conditions. This includes CFD simulations and experimental data comparisons, employing methods aligned with our fundamental research in this area. Furthermore, our work paves the way for integrating these advanced fluid dynamics models into the evolving field of process digitalization, thereby contributing to the development of more efficient, digitally integrated manufacturing processes.